Perception of Females About the Causes Of Obesity in Jaffna - Anpuchelvi, S.; Sritharan, G. (South Eastern University of Sri Lanka, 2013)
Obesity is often defined simply as a condition of abnormal or excessive fat accumulation in adipose tissue to the extent that health may be impaired. Obesity is a risk factor for a number of non-communicable diseases and there has been an increased awareness of the problem in recent years. It is also steadily rising among all age groups. For young females it is a crucial period of life when their status of nutrition will initiate them to become healthy mothers of healthy offsprings. Therefore it is vital that young females remain healthy with the right body weight, eating habits, behavioral pattern and body image perception. Hence this study is undertaken to estimate the prevalence of obesity among female of reproductive age (14-42 years) and to study their knowledge on causes and prevention of the obesity. Community based cross sectional survey was conducted using 336 females aged between 14 - 42 years for a three month duration in Jaffna. A house- to- house visit was conducted and verbal consent of each respondent of the study population was taken. The individuals were interviewed with a pre- designed, pre-tested, semi- structured questionnaire. All questions were open- ended and were asked in the Tamil language. Height in meters and weight in Kg of each person was recorded as per the standard techniques, and the Body Mass index was calculated. Of the study population, 114 (33.9%) females were in the age group of 14- 29 years while 222 (66.1%) were in the age group of 30- 42 years. Females having Body Mass Index equal or more than 28.6 Kg/m2 was considered as obese. The study revealed that 9 (2.7%) female were obese whereas 327 (97.3%) were non obese. It was also identified that the females are quite knowledgeable about the prevention of obesity but emphasis should be given to educate the female about the importance of intake of balanced diet and daily exercise.
Keywords: Body Mass Index; Jaffna; Non-Communicable Diseases; Obesity